Teachers' and students' perceptions towards digital humanities in the English as a foreign language (EFL) teaching and learning - Salsabilah, Farah Tasya; Emaliana, Ive; Sutiyarti, Ulfah; Setiawati, Eti (LITERA, 2024)
Education is starting to move from the conventional to the digital world. One form of this change is the presence of Digital Humanities in the world of education. Digital humanities can provide many benefits, especially in English teaching and learning. This study aims to investigate teachers' and students' perceptions towards digital humanities in the EFL classes. This study was conducted with 103 teachers and students from various schools and universities in Indonesia. In a quantitative phase, a survey questionnaire was distributed to collect the data. The 63 question items are divided into 6 parts: demographics, experiential learning, multimodal communication, digital ethics & critical inquiry, collaborative learning, and AI for language teaching and learning. Moreover, a semi-structured interview was obtained to get details about digital tools and technologies implementation in the EFL teaching and learning. The study revealed that the use of digital humanities effectively enhance EFL teaching and learning. Digital humanities offer a dynamic learning environment for English language learners, providing access to a wealth of resources and tools while streamlining administrative processes for teachers. These findings are align with the intended purpose of digital humanities in classroom, which is to enhance efficiency and accessibility in information retrieval.